Measurements of endolymphatic K⁺ concentrations in the utricle of pre- and postnatal Slc26a4 /+ and Slc26a4 mice - Zhou, Fei (Kansas State University, 2015)
SLC26A4 and its murine ortholog Slc26a4 code for pendrin, an anion-exchanger that is expressed in the inner ear. Patients with mutations in SLC26A4 have syndromic or nonsyndromic hearing loss that is associated with a prenatal enlargement of the membranous labyrinth. The mouse model Slc26a4[superscript]Δ/Δ recapitulates the enlargement, develops an enlargement of the inner ear and fails to acquire hearing. The vestibular labyrinth secretes fluid, accounting for enlargement of the membranous labyrinth. The objective of the current study was to measure K⁺ concentrations in the utricular endolymph of Slc26a4[superscript]Δ/+ and Slc26a4[superscript]Δ/Δ mice as a first step toward a mechanistic understanding of fluid secretion during perinatal development. Doublebarreled K⁺-selective electrodes were used to measure K⁺ concentrations of the utricular endolymph in vitro. Potassium concentrations were ~10 mM in both genotypes at embryonic (E) day 16.5. The K⁺ concentrations started to rise at E17.5 in Slc26a4[superscript]Δ/+ mice. There was a 1-day delay in Slc26a4[superscript]Δ/Δ mice. This delay may be the consequence of a larger fluid volume. K⁺ concentrations rose to 150 mM and 132 mM in Slc26a4[superscript]Δ/+ and Slc26a4[superscript]Δ/Δ adult mice, respectively. Consistently, expression of KCNQ1 and the Na⁺/2Cl⁻/K⁺ cotransporter SLC12A2 was found in the utricle at E19.5 in Slc26a4[superscript]Δ/+ and Slc26a4[superscript]Δ/Δ mice. In conclusion, the data suggest that K⁺ secretion is not the major driving force of fluid secretion in the utricle of the developing mouse inner ear.
Measurements of endolymphatic K⁺ concentrations in the utricle of pre- and postnatal Slc26a4 Δ/+ and Slc26a4 Δ/Δ mice
Keywords: Pendred syndrome; Enlarged vestibular aqueduct; Potassium-selective electrodes; Utricular endolymph